Implementation of Marketing Strategy For Wooden Batik Business Development: Opportunities For Cultural Preservation And Youth Market Target - Vivia Agripina; Eka Sari; Zahra Aulia Raihani; Anggita Tazkia Aulia Rahman; Siti Nur Khaula Sofia; Agrelya Margaretha Carolina Hutapea (Global Sustainability Research Institute, 2025)
Introduction Indonesia is known for its rich arts and culture, one of which is batik. Innovations such as wooden batik open up new opportunities to combine traditional art with the modern market. Batik Kayu Dewi, located in Bogor, is a creative industry player developing wooden batik products. This study aims to examine marketing strategies, product innovations, and challenges faced by Batik Kayu Dewi in maintaining its existence and competitiveness in the modern market. Methods This study uses a qualitative approach with data collection methods that include interviews, direct observation, and documentation. Interviews were conducted with business owners and several parties involved in production and marketing activities. Observations were conducted at production and marketing locations, while documentation includes visual archives and records of business activities. Results The research findings show that Batik Kayu Dewi utilizes several marketing strategies, including through social media, organizing educational workshops, and collaborating with Imah Kramik as a partner in expanding the market network. Innovations made include the use of resin to increase the aesthetic and functional value of the product. However, Batik Kayu Dewi also faces several challenges, such as limited human resources (HR), access to raw materials, and low interest of the younger generation in traditional arts such as wooden batik. Conclusion and Suggestion This study concludes that although Batik Kayu Dewi has succeeded in combining traditional elements with a modern approach through innovation and marketing strategies, business sustainability still faces internal and external obstacles. Therefore, it is recommended that Batik Kayu Dewi develop educational digital content to attract the interest of the younger generation, seek local sources of raw materials to reduce external dependence, and create contemporary product designs to expand the market. These steps are expected to strengthen Batik Kayu Dewi's position in preserving culture while maintaining its competitiveness in the modern market.